2004
DOI: 10.1128/mcb.24.14.6476-6487.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diazaborine Treatment of Yeast Cells Inhibits Maturation of the 60S Ribosomal Subunit

Abstract: Diazaborine treatment of yeast cells was shown previously to cause accumulation of aberrant, 3-elongated mRNAs. Here we demonstrate that the drug inhibits maturation of rRNAs for the large ribosomal subunit. Pulse-chase analyses showed that the processing of the 27S pre-rRNA to consecutive species was blocked in the drug-treated wild-type strain. The steady-state level of the 7S pre-rRNA was clearly reduced after short-term treatment with the inhibitor. At the same time an increase of the 35S pre-rRNA was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 52 publications
2
30
0
1
Order By: Relevance
“…Recently we demonstrated that the 60S ribosomal subunit formation defects caused by the drug diazaborine are compensated for by allelic forms of Drg1 (24). To test whether Drg1 plays a role in ribosome biogenesis, we obtained polysome profiles from the temperature-sensitive drg1-ts strain, the intragenic suppressor strain (drg1-sup), and the isogenic wild-type strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently we demonstrated that the 60S ribosomal subunit formation defects caused by the drug diazaborine are compensated for by allelic forms of Drg1 (24). To test whether Drg1 plays a role in ribosome biogenesis, we obtained polysome profiles from the temperature-sensitive drg1-ts strain, the intragenic suppressor strain (drg1-sup), and the isogenic wild-type strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were suspended in 5 M guanidinium-HCl buffer and broken by vigorous vortexing with glass beads. RNA was extracted and transferred onto nylon membranes as described previously (24). After UV cross-linking, the radioactivity on the membrane was detected by phosphorimaging using a tritium screen (Kodak).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed previously that the drug diazaborine blocks ribosome biogenesis in yeast (10). Diazaborine is a heterocyclic boron-containing compound with strong antimicrobial activity (11).…”
mentioning
confidence: 99%